Keragaman Molekuler Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) Varietas MTG (Moderat Tahan Gano) Berdasarkan Primer SSR (Simple Sequence Repeats) - Rika Hardianti; Lollie Agustina P. Putri; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2017)
The  aim of the research was to analyze molecular diversity of oil palm MTG variety (Moderate Tahan Gano) with SSR primer. This research was conducted in Plant Tissue Culture Laboratory of  Agriculture, University of  Sumatera Utara and Bio Molecular Laboratory of SSPL (Socfindo Seed Production and Laboratories) Bangun Bandar, Dolok Masihul, Serdang Bedagai-  Sumatera Utara, from February to  September 2016. Individuals were observed as many as 27 samples of oil palm crop varieties MTG issued by PT. Socfin Indonesia using SSR primer. Dendogram formation program conducted with the help of Darwin 6.0.13. The results showed that the percentage of polymorphic 100% and analysis of phylogenetic dendodgram divided into 3 main groups consisting of two sub-groups of 27 samples analyzed.   Keywords: molecular diversity, MTG variety, oil palm, SSR primer.